2014
DOI: 10.3109/03009734.2014.895786
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin-derived amyloidosis: Probably a common cause of lumbar spinal stenosis

Abstract: Background Senile systemic amyloidosis (SSA) derived from wild-type transthyretin is a fairly common condition of old individuals, particularly men. The main presentation is by cardiac involvement, which can lead to severe restrictive cardiomyopathy. SSA is, however, a systemic disease, and amyloid deposits may appear in many other tissues but are thought to be without clinical symptoms outside the heart. Amyloid is a very common finding in cartilage and ligaments of elderly subjects, and transthyretin has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 37 publications
(33 reference statements)
1
84
0
4
Order By: Relevance
“…These features of transthyretin amyloid deposits in the ligamentum flavum were consistent with a few previous reports that evaluated smaller numbers of lumbar spinal canal stenosis patients. 13,14,22 In addition, because we discovered no relationship between the amount of transthyretin amyloid and age, we speculate that aging mainly affects the initiation of transthyretin amyloid formation in the ligamentum flavum. Because we found no symptoms that would indicate cardiac amyloidosis, which is major symptom of senile systemic amyloidosis, an age-related systemic form of amyloidosis, transthyretin-positive amyloid deposition in the ligamentum flavum of lumbar spinal canal stenosis patients may be a localized form of amyloidosis.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These features of transthyretin amyloid deposits in the ligamentum flavum were consistent with a few previous reports that evaluated smaller numbers of lumbar spinal canal stenosis patients. 13,14,22 In addition, because we discovered no relationship between the amount of transthyretin amyloid and age, we speculate that aging mainly affects the initiation of transthyretin amyloid formation in the ligamentum flavum. Because we found no symptoms that would indicate cardiac amyloidosis, which is major symptom of senile systemic amyloidosis, an age-related systemic form of amyloidosis, transthyretin-positive amyloid deposition in the ligamentum flavum of lumbar spinal canal stenosis patients may be a localized form of amyloidosis.…”
Section: Discussionmentioning
confidence: 81%
“…13 Another recent paper suggested that transthyretin amyloid formation may be a common cause of lumbar spinal canal stenosis. 14 We also reported that a senile systemic amyloidosis patient with multifocal spinal transthyretin amyloid deposits developed severe destructive spondylosis and radiculomyelopathy. 15 However, how amyloid deposits in the ligamentum flavum affect lumbar spinal canal stenosis in which the ligamentum flavum shows degeneration and hypertrophy remains unclear.…”
mentioning
confidence: 82%
“…8,9 Recently, ATTRwt-CA is increasingly recognized as a cause of various common diseases. While ATTRwt-CA was identified in 13% of elderly patients (>60 years old) with HFpEF and 16% of patients undergoing transcatheter aortic valve replacement, respectively, 2,4 bilateral carpal tunnel syndrome (CTS) and lumbar spinal stenosis frequently present many years before the development of cardiac symptoms.. 10,11 Hereditary ATTR-CA (ATTRv-CA) is an autosomal-dominant disease in which gene mutations lead to changes in the protein TTR. 12 More than 120 mutations have been reported in the TTR gene with considerable phenotypic and geographical heterogeneity.…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%
“…Lumbar spinal stenosis, the most common indication for back surgery in older adults, may represent yet another potential manifestation of systemic amyloid deposition. In one study of patients who underwent surgery spinal stenosis, 21 of 26 specimens demonstrated amyloid deposition . Of the 15 specimens suitable for immunohistochemical staining, five demonstrated positive TTR immunoreactivity.…”
Section: Diagnosismentioning
confidence: 99%